Signals for change: A regional examination of rural clinical trial participant perspectives on values, health behaviors, and motivations for enrollment and retention in remote settings - Elizabeth A. Johnson; Danika L. Comey; Bernadette McCrory (Journal of Clinical and Translational Science)
There is a known disparity in clinical trial enrollment of rural-dwelling residents in the United States, largely due to financial constraints and travel burden. A big data study of an Intermountain West rural-serving healthcare system reported strong retention rates of historically underrepresented populations with adapted approaches. This exploratory qualitative descriptive study describes the lived experience and perceptions of eleven rural residents who participated or were interested in clinical trials from this healthcare system. Thematic analysis of interviews identified co-existing dualities between culture and traditional trial models, which suggest adapted designs are necessary to achieve opportunity equity in rural regions.